2016
DOI: 10.17795/zjrms-5027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Enriched Bread Intake on the Oxidative Stress Indices in Male Wistar Rats

Abstract: Background: Contrary to the proven benefits of iron, few concerns in producing the oxidative stress is remained problematic. Objectives: The aim of the study was to evaluate the oxidative stress in the male Wistar rats fed bread supplemented with iron in different doses i.e., 35 (basic), 70 (two fold), 140 (four fold), and 210 mg/kg (six fold) with or without NaHCO3 (250 mg/kg). Methods: In this experimental study Iron, ceruloplasmin, ferritin, total iron binding capacity (TIBC), albumin, total protein, uric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this study, no significant difference was found in the total volume or fractional volumes of the cortex or medulla between the experimental and control groups. However, Heidari et al (38), showed that the mean total volume of kidney in 0.13% lead acetate groups, increased compared to the control group in adult male rat. It was significant in groups that received lead acetate in their drinking water for 8 and 12 weeks and not for 4 weeks.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, no significant difference was found in the total volume or fractional volumes of the cortex or medulla between the experimental and control groups. However, Heidari et al (38), showed that the mean total volume of kidney in 0.13% lead acetate groups, increased compared to the control group in adult male rat. It was significant in groups that received lead acetate in their drinking water for 8 and 12 weeks and not for 4 weeks.…”
Section: Discussionmentioning
confidence: 93%
“…However, renal hypertrophy is not associated with hypertrophy of the glomeruli, and the rise of kidney weight and volume is due to hypertrophy of the proximal tubules (39), which is due to protein synthesis in these areas (38). Goyer et al (45) showed no changes in glomeruli, while signs of changes in glomerular cells became apparent 6 weeks after lead administration in rat.…”
Section: Discussionmentioning
confidence: 99%